2018
DOI: 10.1089/fpd.2018.2440
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Simulated Commercial Frying Process to ControlSalmonellain Donuts

Abstract: This study validated a typical commercial donut frying process as an effective kill-step against a 7-serovar Salmonella cocktail (Newport, Typhimurium, Senftenberg, Tennessee, and three dry food isolates) when contamination was introduced through inoculated flour. The bread and pastry flour mix (3:1) was inoculated with the Salmonella cocktail, and subsequently dried back to original preinoculation moisture content, achieving a Salmonella population of 7.6 log CFU/g. Inoculated flour was used to prepare a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…The differences in the D ‐values of Salmonella in the current study and that of Channaiah et al. (2016, 2017, 2018) can be attributed to the different Salmonella serovars used and the differences in the chemical/nutrient composition of the products used in these studies. In general, with the increase in fat, protein and sugar content of products, the thermal resistance of microorganisms also increases.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…The differences in the D ‐values of Salmonella in the current study and that of Channaiah et al. (2016, 2017, 2018) can be attributed to the different Salmonella serovars used and the differences in the chemical/nutrient composition of the products used in these studies. In general, with the increase in fat, protein and sugar content of products, the thermal resistance of microorganisms also increases.…”
Section: Resultscontrasting
confidence: 67%
“…In another validation study, Channaiah et al. (2018) reported that frying donuts in oil at 190.6°C for 2 min (1 min on each side) resulted in >7 log reductions in 7‐serovar Salmonella cocktail population (Newport, Typhimurium, Senftenberg, Tennessee and three dry food isolates) and the internal donut temperature reached to ~119°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies to date on the quality of the donuts are related to prevention of acrylamide formation during the frying process [26], reduction in oil absorption during the frying process [27], the effects of different process parameters (frying mode, temperature and time) [28], formulation [29] and type and quality of frying oil [30]. However, there are few studies focused on the direct incorporation of plant-based antioxidants in donut formulation to retard acrylamide formation during the frying process [26].…”
Section: Introductionmentioning
confidence: 99%